Three new species of Anacroneuria (Plecoptera: Perlidae) from Centre-West and Southeast Brazil - Righi-Cavallaro, Karina O.; Lecci, Lucas S. (Zootaxa, 2010)
Three new species of Anacroneuria are described herein: A. otafroehlichi sp. n., A. terere sp. n. and A. singularis sp. n. In addition, we report the presence of A. atrifrons Klapálek and A. pastaza Stark for the first time in Mato Grosso do Sul State. The reported distributions of A. payagua Froehlich and A. ofaye Froehlich are expanded into Mato Grosso do Sul State.